Improving Students' Speaking Skill by Using Task Based Learning Technique at First Semester of English Education Study Program STAIN Bengkalis - Kurniati Kurniati; Ervina Ervina; Titin Sumarni (Akademika: Jurnal Keagamaan dan Pendidikan, 2023)
This research aims to explain the extent to which task based learning (TBL) technique can improve the students’ speaking skill and what factors that influence the changes of the students’ speaking skill by implementing TBL technique. This research is a classroom action research (CAR), which was conducted in two cycles. The instruments that were used to collect the data were speaking test, observation sheet, field notes, and interview guide. The data were analyzed quantitatively and qualitatively. The findings reveal that the implementation of TBL technique can improve the students’ speaking skill at first semester of English Education Study Program STAIN Bengkalis. It was showed from the students’ average score. The mean score before conducting the research was 2.62, the mean score of cycle 1 was 2.98, and the mean score of cycle 2 was 3.38. Besides, this research also found the factors that influence the changes of the students’ speaking skill by implementing TBL technique namely, real world material, interaction, and lecturer’s role. Therefore, it can be concluded that TBL technique is effective in teaching speaking. While, real world material, interaction, and lecturer’s role influence the improvement of the students’ speaking skill at first semester of TBI.